The Effect of Kangaroo Mother Care Method toward Weight Gain and Length of Stay among Low Birth Weight Baby - Muliani Muliani; Lisnawati Lisnawati (Intelektual Pustaka Media Utama, 2018)
Infant mortality needs to get serious attention. Special efforts are relatively easy and inexpensive in the handling and care is through treatment methods can improve the stability ofKangaroo Mother Care(KMC) for babies and breastfeeding.The effort hopefully will contribute to weight gain which take effect on the duration of treatment. The study design was Quasi Experiment with Prepost one group design. Samples were mothers with a history of low birth weight deliveries, with sample selection technique in consecutive sampling and sample number 36 babies. The samples criteria were infants birth weight between 1,000-2,100 gr, weight of infant when KMC was started between 900-2,100 gr, weight of infants post KMC were 1,300-2,500 gr, babies born with premature or small period of pregnancy. KMC method has the potential to improve the Weight on Low Birth Weight (LBW).Duration of KMC has no effect on weight gain but can accelerate the length of LBW in hospital. The longer do KMC, the shorter duration of hospital LBW in hospital. LBW should be treated KMC to accelerate weight gain and reducing the length of hospitalization.